Anxiety and Academic Performance among Private Medical College Students - Das, Shila Rani; Biswas, Chinmay (Journal of Current and Advance Medical Research, 2018)
Background: Medical students are in a huge pressure due to their academic syllabus. Objective: The purpose of the present study was to assess the relationship between anxiety and academic performance among private medical college. Methodology: This cross sectional study was done in private medical College Hospital, Dhaka, Bangladesh and 3rd and 4th year medical student were included. Data was collected by using semi structured Socio-demographic questionnaire and Burn Anxiety Inventory scale and Checklist. Finally all data and results were analyzed using latest version of SPSS software. For descriptive statistics means, medians, SD and range will be calculated as required. Data will be presented in frequency table, bar, pie and scattered diagram as per need. Statistical test chi-square test were used and p<0.05 was consider to be statistically significant. Results: A total number of 200 medical students were studied after fulfilling the inclusion and exclusion criteria. Among them 87.0% were Muslim; 98.0% were unmarried; 83.0% were in nuclear family; family member of 42.5% respondents had 4 to 6 persons; monthly income of 64.7% respondents were less than 50,000 Taka; 47.0% of the respondents’ father occupation was businessman. In 1st profession examination 68.0% in Anatomy, 73% in Physiology, 76% in Biochemistry were passed in anatomy. In 1st professional exam, students suffered from moderate to extreme anxiety were passed 78% and referred 22% as well as suffered from minimal to mild anxiety were passed 43% and referred 57% in Physiology. So there was strong association between the two variables (p<0.05). Conclusion: Three fifth of the students are suffered from moderate anxiety level and those who are suffered moderate to extreme anxiety passed more and their class attendance are good. Journal of Current and Advance Medical Research 2018;5(2):68-72